Investigation and analysis of carbapenem-resistant gram-negative bacterial infection rates across hospitals in Shandong Province in China - Liu, Keke; Xu, Hua; Sun, Jian; Liu, Yuqing; Li, Weiguang (Frontiers in Public Health, 2022)
Background: The increasing incidence of carbapenem‑resistant bacterial infections has become a serious public health threat. This study aimed to investigate and analyze the current regional differences in carbapenem-resistant gram-negative bacteria (CRGN) in a major province of China, and provide suggestions for preventing hospital infections. Methods: A questionnaire survey was used to obtain the current data on CRGN from 36 hospitals in Shandong province, China, from 2019 to 2020. The association between the detection rates and discovery rates of CRGN and the use of antibacterial drugs was analyzed using Spearman’s correlation coefficient. In addition, we compared the detection rates of CRGN and antibacterial drugs using hospitals categorized according to different levels and economic areas using the Kruskal-Wallis test. Results: The detection rates of CRGN across the 36 hospitals varied from 1.19% to 52.07%. The discovery rate of carbapenem-resistant Enterobacteriaceae (CRE) and carbapenem-resistant Acinetobacter baumannii (CRAB) remained below 5‰, and that of carbapenem-resistant Pseudomonas aeruginosa (CRPA) was below 10‰. Except for CRAB, the correlations between the detection rate and antimicrobial drug use intensity and carbapenem drug use percentage were 0.11-0.29 and 0.31-0.47, respectively. Carbapenem drug use was higher in the provincial hospital group than in the prefecture-level hospitals (P<0.05), and that in the high-economic regional hospital group was higher than in the low-economic regional hospital group (P<0.05). Conclusions: The detection and discovery rates of CRE were low, and those of CRAB were high in Shandong province. Larger hospitals have higher carbapenem drug use. These results can be used as a reference for preventing CRGN infections in developing countries and provide a basis for regional carbapenem resistance prevention and control strategies.